2022
DOI: 10.1038/s41598-022-14383-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing wind direction prediction of South Africa wind energy hotspots with Bayesian mixture modeling

Abstract: Wind energy production depends not only on wind speed but also on wind direction. Thus, predicting and estimating the wind direction for sites accurately will enhance measuring the wind energy potential. The uncertain nature of wind direction can be presented through probability distributions and Bayesian analysis can improve the modeling of the wind direction using the contribution of the prior knowledge to update the empirical shreds of evidence. This must align with the nature of the empirical evidence as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…CONCLUSION The benefits of this research were to achieve possible application of low-cost small-scale wind turbine in South Africa for low wind speed areas, thereby providing low-cost electricity to households and inhabitants in urban as well as in rural areas for a very large region in South Africa. This was achieved by developing a test prototype for low wind speed condition in Soweto, Johannesburg, South Africa, and Moreover prediction case study using Soweto test results were shared in number (2). Finally, a predictive case study for the Eastern Cape, focused on the Gqeberha (PE) area, was conducted using the empirically obtained data for the Soweto and Gqeberha (PE) areas, and it was concluded that it would be feasible to implement the Soweto technology in Port Elizabeth due to the results emanating presumably from the conditions at lower altitude (higher density air), and much higher wind speed resources at or near the coastal region.…”
Section: Datementioning
confidence: 99%
See 1 more Smart Citation
“…CONCLUSION The benefits of this research were to achieve possible application of low-cost small-scale wind turbine in South Africa for low wind speed areas, thereby providing low-cost electricity to households and inhabitants in urban as well as in rural areas for a very large region in South Africa. This was achieved by developing a test prototype for low wind speed condition in Soweto, Johannesburg, South Africa, and Moreover prediction case study using Soweto test results were shared in number (2). Finally, a predictive case study for the Eastern Cape, focused on the Gqeberha (PE) area, was conducted using the empirically obtained data for the Soweto and Gqeberha (PE) areas, and it was concluded that it would be feasible to implement the Soweto technology in Port Elizabeth due to the results emanating presumably from the conditions at lower altitude (higher density air), and much higher wind speed resources at or near the coastal region.…”
Section: Datementioning
confidence: 99%
“…South Africa's climatology allows for significant wind energy production especially along the coastal areas of the Eastern and Western Capes. The first large-scale wind farm in South Africa became operational in 2014 and based on the SAWEA report, there are 33 wind farms: 22 fully operational and 11 in constructions [2]. Amidst rising demands for decarbonization and sustainability in the 3 rd world.…”
Section: Introductionmentioning
confidence: 99%
“…Cleaner and more sustainable solutions for long-term development are emerging as promising solutions [1,2]. Wind energy production is growing more significantly than any other type and plays an important role in the energy supply of modern systems [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%